2015
DOI: 10.1038/ncomms9261
|View full text |Cite
|
Sign up to set email alerts
|

eIF6 coordinates insulin sensitivity and lipid metabolism by coupling translation to transcription

Abstract: Insulin regulates glycaemia, lipogenesis and increases mRNA translation. Cells with reduced eukaryotic initiation factor 6 (eIF6) do not increase translation in response to insulin. The role of insulin-regulated translation is unknown. Here we show that reduction of insulin-regulated translation in mice heterozygous for eIF6 results in normal glycaemia, but less blood cholesterol and triglycerides. eIF6 controls fatty acid synthesis and glycolysis in a cell autonomous fashion. eIF6 acts by exerting translation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
119
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(134 citation statements)
references
References 68 publications
13
119
0
Order By: Relevance
“…Other snoRNAs were not changed (Fig 4F; S1 and S2 Files). Intriguingly, there was no overlap between the genes regulated at the polysomal level by Sbds mutation (S1 File), to the ones we previously found regulated by eIF6 deficiency [41]. …”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Other snoRNAs were not changed (Fig 4F; S1 and S2 Files). Intriguingly, there was no overlap between the genes regulated at the polysomal level by Sbds mutation (S1 File), to the ones we previously found regulated by eIF6 deficiency [41]. …”
Section: Resultsmentioning
confidence: 77%
“…We focused our attention on information deriving from LINCS/CMap project to evaluate if the gene expression profile found altered in the total fraction of Sbds R126T/R126T MEFs cells was similar to transcriptional changes induced by drugs, observed in other cell types and to eIF6 deficiency [41]. Analysis performed by Query web tool on the complete list of modulated genes, and on a subset of the most changed ones identifies three common PKC activators: ingenol, phorbol-12-myristate-13-acetate and prostratin (S3 File).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, differences in the abundance of proteins, such as eIF6, between WT and Lck −/− T cells may have influenced the range of mRNA species that are translated. The antiassociation factor eIF6 prevents premature binding of 40S and 60S ribosome subunits (38) and has been shown to affect G1/S cell cycle transition (39,40) and the expression of metabolic enzymes controlling fatty acid synthesis and glycolysis (41). A G1/S block was observed in Lck −/− cells at 24 h after stimulation, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that fatty acid metabolism was highly enriched in the translationally repressed gene subset in Lck −/− cells.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of Tif6 in yeast results in loss of 60S ribosome, which can be rescued by ectopic expression of human eIF6 (42)(43)(44), suggesting a possible role of eIF6 in ribosome biogenesis in mammalian cells. eIF6 is also known to regulate translation of a subset of mRNAs containing upstream (u)ORF motifs in their 5′ UTR (41). Overexpression of eIF6 in a murine mast cell line enhanced the production of IL-2 (45), which contains uORF in its transcript (46).…”
Section: Discussionmentioning
confidence: 99%